PP76 Chemical and Antimicrobial Potential of Endophytic Fungi from Tibouchina urivellana - Martínez Vargas, Jeisson Javier; QUIROGA, Daniel Felipe; LEGUIZAMÓN, Gabriel Esteban; Plazas Gonzalez, Erika Andrea (Revista Productos Naturales, 2025)
Endophytic fungi are symbiotic microorganisms that reside the internal tissues of plantas, and have coevolved with their hosts, developing remarkable biosynthetic capabilities to produce complex secondary metabolites with remarkable antimicrobial, antiviral, and anticancer potential